Reconstructing Islamic Character Education through Tafsir Responsive: An Empirical Investigation - Mukhlisin Mukhlisin; Abdul Hanan; Muhammad Permadi; Abdurrahman Atsa’lawi (Mozaic : Islam Nusantara, 2026)
This study examines the escalating crisis in Islamic character education, reflected in moral deterioration, increasing radical tendencies, and the widening gap between traditional Qur’anic understanding and contemporary social realities. The study aims to reconstruct Islamic character education through the development of Responsive Tafsir as a contextual and integrative pedagogical model of Qur’anic interpretation. A qualitative descriptive case study approach was employed, with data collected over six months through in-depth interviews, participant observation, and document analysis at Pesantren Babakan Cirebon. The findings reveal that Responsive Tafsir is built upon three principal foundations: maqasid-based interpretation, contextual hermeneutics, and the Living Qur’an approach. These elements transform tafsir into a dynamic, practice-oriented educational pedagogy. Its implementation is reflected in thematic learning, dialogical interaction, contextual application, and collaborative interpretation, all of which encourage active student participation and deeper value internalization. Empirically, the model contributes to the development of key character dimensions, including religious moderation, social awareness, intellectual integrity, empathy, and moral autonomy. The study further demonstrates that Responsive Tafsir functions as an educational strategy to counter radicalism by cultivating students’ critical and contextual interpretive capacities. Conceptually, this study positions Responsive Tafsir not as a grand theory, but as a pedagogical model that bridges classical Islamic scholarship with contemporary educational needs. Therefore, Islamic educational institutions are encouraged to adopt this pedagogical approach by strengthening contextual interpretation practices and enhancing teachers’ competencies in responsive hermeneutics to support sustainable character development.